In Vitro effect of angelica (Angelica archangelica L.) hydrolate on soybean (Glycine max L. Merr.) and winter wheat (Triticum aestivum L.) seed germination: In Vitro efekat hidrolata angelike (Angelica archangelica L.) na klijavost semena soje (Glycine max L. Merr.) i ozime pšenice (Triticum aestivum L.) - Lazarević, Jovan; Knežević, Isidora; Matković Stojšin, Mirela; Stevanović, Dragana; Brković, Predrag; Damnjanović, Jelena (Acta herbologica, 2026)
Soybean (Glycine max L. Merr.) and winter wheat (Triticum aestivum L.) are one of the key agricultural crops whose germination and early growth are crucial for achieving high yields. In this study, the biostimulant potential of Angelica archangelica hydrolate, a by-product obtained during essential oil distillation, was evaluated on soybean and winter wheat seeds. Seeds were treated with hydrolate solutions of different concentrations (0,25%, 0,5%, 1%, 5%, and 10%), and germination tests were conducted under controlled laboratory conditions. Results showed that hydrolate treatments significantly increased seedling length in both crops compared to the control. The highest growth was recorded at the 10% concentration for both soybean (5,77 cm) and wheat (3,13 cm). Lower concentrations also improved growth, though with less pronounced effects. These findings confirm that A. archangelica hydrolate positively influences germination and early seedling development, suggesting its potential use as a natural biostimulant in sustainable agriculture. Since hydrolates are environmentally safe and underexplored in agricultural practice, further research under field conditions is necessary to optimize their application and fully exploit their potential in promoting plant growth.